Cities, mobility and environment in EU strategies and research projects - Galderisi, Adriana (TeMA - Journal of Land Use, Mobility and Environment, 2008)
During the last decade, a central role in EU strategies and research programs has been assigned to the relation among cities, mobility and environment. Namely, the setting up of policies for increasing mobility, reducing its adverse impacts, has been assumed as one of the main European goal for gaining the challenge of international competition. Hence, from the end of the Nineties, the EU addressed its efforts towards the identification of innovative solutions for a sustainable urban mobility, promoting research and initiatives in multiple areas, from transport infrastructures to traffic management, from public transport services to urban planning. The European documents set up starting from 2000, the results achieved by the European research and the guidelines provided by the Seventh Framework Programme point out the need for overcoming the sectorial approach which has for long characterized transport planning and policies. At present, grounding on integrated approaches, new ideas and practices are emerging, driving towards a closer relation between transport planning and land use planning at different scales. Nevertheless, in the European strategies and researches, the solution to the difficult relation among cities, mobility and environment is, up to now, mainly committed to the integration among sectorial policies grounded on knowledge and competencies still very far one from each other. The awareness that an effective integration requires new areas of interdisciplinary thinking and competencies and innovative practices and tools, is still weak.